2017
DOI: 10.1002/acr.23082
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Features of the First Metatarsophalangeal Joint in Gout and Asymptomatic Hyperuricemia: Comparison With Normouricemic Individuals

Abstract: Urate deposition, synovitis, and bone erosion are common at the MTP1 joint in people with gout, even in the absence of flare. Although individuals with asymptomatic hyperuricemia lack ultrasound features of inflammation or structural joint changes, they demonstrate a similar frequency of urate deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Numerous controlled studies of joints in healthy, asymptomatic people have demonstrated the presence of MIFFS . They occur quite commonly.…”
Section: Miffs In Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous controlled studies of joints in healthy, asymptomatic people have demonstrated the presence of MIFFS . They occur quite commonly.…”
Section: Miffs In Healthy Controlsmentioning
confidence: 99%
“…For instance, disk degeneration can be found in up to 37% of healthy, asymptomatic 20‐year‐old subjects and the prevalence rises to 96% of people in their 80s . Many MIFFS resemble what one would expect to see in hemophilia patients, such as synovitis, cartilage erosion and subchondral cysts . This begs the question, are the MIFFS seen in hemophilia joints due to bleeding, or are they a part of the natural aging process?…”
Section: Miffs In Healthy Controlsmentioning
confidence: 99%
“…In addition, synovial lesion (i.e., synovial hypertrophy and synovitis) and bone erosion are also regularly detected by ultrasound in gout and hyperuricemia patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Gout is a common inflammatory disease induced by deposition of monosodium urate (MSU) crystals in joints and surrounding soft tissues. Although hyperuricemia is required for development of symptomatic gout, majority of patients with hyperuricemia do not suffer gouty arthritis, even MUS crystals are detected in joints (1,2). Chronic pain, soreness or numbness in the joints are reported in some patients without convincing clinical evidence of gouty attack.…”
Section: Introductionmentioning
confidence: 99%
“…But there is a lack of studies investigating the relationship between the clinical symptoms and spread of US findings in gout. The studies with asymptomatic hyperuricemia [12,13] or gout studies investigating both: the symptomatic and the contralateral joint [14] showed that T, double contour (DC), and even erosions (E) can be found in the joint, in which symptoms have never been reported, raising the question of concordance between the clinics and US changes. Which joints should be investigated for gout classification, just the symptomatic joints or more, independently of symptoms, this is still a matter of discussion.…”
Section: Introductionmentioning
confidence: 99%